Comparison of stress tolerance of hybrid and selfed offspring of two populations of Litopenaeus vannamei - Shi, Miao; Jiang, Song; Jiang, Shigui; Yang, Qibin; Li, Yundong; Zhou, Falin (Frontiers in Marine Science, 2023)
Litopenaeus vannamei collected from Thailand (T) and the United States (M) were used as parents, while four progeny populations of TT, MM, TM, and MT were constructed by diallel cross, with a total of 20 families. The tolerance of young shrimp to high ammonia-N, high pH, and low salt was compared through a 96-h acute toxicity test; the heterosis of each mating combination was analyzed; and the tolerance of parents and offspring was evaluated. Here we show that under 96 h of high ammonia-N, high pH, and low salt stress, the mortality rates of each family were 19.52%-92.22%, 23.33%-92.22%, and 19.33%-80.00%, respectively. There were significant differences in the tolerance of different families to ammonia-N, pH, and salinity stress (P < 0.05). The population with a female parent from the United States had stronger tolerance to ammonia-N, pH, and low salt stress than the population with a female parent from Thailand. The population with a male parent from Thailand had weaker tolerance to pH and low salt stress than the population with a male parent from the United States, but it was superior to the population with a male parent from the United States under ammonia-N stress. The heterosis rates of the hybrid population TM in acute high ammonia-N, high pH and low salinity were 81.67%, 44.58% and −10.13%, respectively; However, the heterosis rates of the MT population were 14.89%, 38.89%, and −8.96%, respectively. The overall resistance of the four populations showed MM > MT > TT > TM. The population TM had obvious heterosis in high ammonia-N and high pH tolerance traits, and the family MM7 had a strong low salt tolerance, so it can be considered a candidate family for subsequent breeding work. The experimental results provide a basis for screening new strains of Vannamei shrimp with strong stress resistance through family breeding.